Pengaruh Asimetri Informasi Terhadap Manajemen Laba dengan Ukuran Perusahaan dan Kepemilikan Manajerial Sebagai Variabel Pemoderasi - Ningtyas, Arie Dea; Mukhzarudfa, Mukhzarudfa; Kusumastuti, Ratih (Jurnal Akuntansi & Keuangan Unja, 2025)
This research aims to analyze the effect of Information Asymmetry on Earning Management With Firm Size and Managerial Ownership as Moderating Variables in Property and Real Estate Companies listed on the Indonesia Stock Exchange from 2021 to 2024. The research method used is Moderated Regression Analysis (MRA). The population in this study consists of all property and real estate companies listed on the Indonesia Stock Exchange, With Sample Selection based on specific criteria. The results indicate that Information Asymmetry, Firm Size, and Managerial Ownership have an Influence on Earnings Management. In Addition, The Moderated Regression Analysis reveals that Firm Size and Managerial Ownership are able to Moderate the effect of information asymmetry on Earning Management in Property and Real Estate Companies Listed on the Indonesia Stock Exchange for the 2021-2024 period. This study implies that reducing information asymmetry is crucial to limiting earnings management practices, particularly in property and real estate companies where firm characteristics play a significant role. Furthermore, the moderating effects of firm size and managerial ownership suggest that stronger internal governance structures can help mitigate opportunistic managerial behavior arising from information gaps.